2010
DOI: 10.1177/1048371309353878
|View full text |Cite
|
Sign up to set email alerts
|

The Brain in Singing and Language

Abstract: This article summarizes currently available brain research concerning relationships between singing and language development. Although this is a new field of investigation, there are findings that are applicable to general music teaching classroom. These findings are presented along with suggestions about how to apply them to teaching music.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
0
6
1
1
Order By: Relevance
“…Singing is a form of social engagement, particularly in the format of a group session, and communicates on multiple levels through physicality, emotions and language (Bannan, 2008). It is suggested that singing can have a positive impact on not only language, but additionally understanding and speech (Trollinger, 2010); evidence from this study does not corroborate this level of impact, but suggests further positive outcomes for engagement in singing.…”
Section: Discussioncontrasting
confidence: 75%
“…Singing is a form of social engagement, particularly in the format of a group session, and communicates on multiple levels through physicality, emotions and language (Bannan, 2008). It is suggested that singing can have a positive impact on not only language, but additionally understanding and speech (Trollinger, 2010); evidence from this study does not corroborate this level of impact, but suggests further positive outcomes for engagement in singing.…”
Section: Discussioncontrasting
confidence: 75%
“…Evidence has been provided that the improved processing of timbre and pitch in musicians is based on functional adaptations, but seems to play a general role in musical development from infancy onwards [ 83 ]. Furthermore, musicians’ improvements in detecting pitch and timbre cues largely rely on plastic adaptations [ 49 , 82 , 84 ]. Language acquisition processes are also based on differentiating timbres of speech that are meaningful and/or meaningless [ 84 ] and for musicians it is also necessary to discriminate timbre differences between various instruments which in turn seem to have an effect on speech sound discrimination as well [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, musicians’ improvements in detecting pitch and timbre cues largely rely on plastic adaptations [ 49 , 82 , 84 ]. Language acquisition processes are also based on differentiating timbres of speech that are meaningful and/or meaningless [ 84 ] and for musicians it is also necessary to discriminate timbre differences between various instruments which in turn seem to have an effect on speech sound discrimination as well [ 82 ]. Evidence for an overlap between processing tonal and verbal material, especially comes from brain research e.g., [ 51 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The brain naturally seeks patterns to make sense of the world. Other articles compared music and language processing and discussed how the development of each could have reciprocal benefits (Cooper 2010;Trollinger 2010).…”
Section: Educational Applicationsmentioning
confidence: 98%